Caracterización fenotípica y morfológica de una población autóctona de la gallina criolla (gallus domésticus l), cantón Pichincha provincia de Manabí - Loor Ormaza, Evelyn Alexi (2017)
The study of the external morphological characteristics of the criolla hen from the Pichincha town, province of Manabí was carried out. The total poultry sample was 475, of which 307 were hens (64.63%) and 168 hens (35.37%). The objectives of the research were: to evaluate the phenotypic diversity and to verify the phenotypic characteristics of an indigenous population of criollo hen (Gallus domesticus L.) 16 quantitative variables and six qualitative variables were evaluated by means of descriptive statistics and dispersion measures. Of the total sample was 3.97 ± 0.04 kg, with a moderate coefficient of variation of 23.06%. Descriptive analysis by sex showed greater weight of roosters with 4.87 ± 0.05 and lower in hens The length, head width, length and width of the ear showed moderate variation, with the exception of length and width of the crest showed high variation (29,30% and 38,16%). The phaneroptic characteristics describe a sample of birds with dominant phenotypes with plumage of dark colors (65.05%), the main ones being: black with red, red, black, marbled and gray. In the distribution of plumage stands the normal (54.32%) and bare neck (34.11%). The type of abundant ridge is simple with 89.00%, frequent crest coloration was red (58.00%), the usual peak color was yellow and black with 53.00% and 44.00%, the Dominant skin color was yellow with 89.68%. The tarsus color with the highest frequency was yellow (63.32) and black 32.63%. The results found will contribute to the knowledge to establish the genetic pattern and will also contribute scientific bases for conservation and promotion of the hen criolla of Ecuador.